2016
DOI: 10.3892/ol.2016.5218
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of the 8q22-24 position in human breast cancer: TSPYL5, MTDH, ATAD2 and CCNE2 genes are implicated in oncogenesis, while WISP1 and EXT1 genes may predict a risk of metastasis

Abstract: Gene expression profiling has been suggested to predict breast cancer outcome. The prognostic value of the 8q22-24 position in breast cancer remains to be elucidated. The present study evaluated expression patterns of the genes located at this position in metastatic and non-metastatic breast cancer. A total of 85 patients with recurrent/metastatic (n=15) and non-metastatic (n=70) early-stage, estrogen receptor-positive and lymph node-negative breast tumors were included. In addition, 15 normal breast tissue sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 43 publications
2
27
1
Order By: Relevance
“…Virtually all tumors with this expression pattern possessed co-amplification of a region on 8q22-24 that includes RPL8, RPL30 and the oncogene MYC. Amplification of this region has been previously described in breast cancers and correlates with chemoresistance and metastasis (Hu et al 2009;Parris et al 2014;Taghavi et al 2016). Our results indicate that this amplification and the ensuing overexpression of RPL8 and RPL30 also occurs in subsets of melanoma, liver, prostate, lung, and head and neck cancers.…”
Section: Discussionsupporting
confidence: 77%
“…Virtually all tumors with this expression pattern possessed co-amplification of a region on 8q22-24 that includes RPL8, RPL30 and the oncogene MYC. Amplification of this region has been previously described in breast cancers and correlates with chemoresistance and metastasis (Hu et al 2009;Parris et al 2014;Taghavi et al 2016). Our results indicate that this amplification and the ensuing overexpression of RPL8 and RPL30 also occurs in subsets of melanoma, liver, prostate, lung, and head and neck cancers.…”
Section: Discussionsupporting
confidence: 77%
“…Some of these mRNAs including WISP1, S1PR1 and SORBS1 have been characterized as oncogenes or tumor suppressors in various cancers. It has been showed that WISP1 gene might be a predictive marker of breast cancer metastasis [39]. Our data also indicated that WISP1 was inversely related to patients overall survival.…”
Section: Discussionsupporting
confidence: 70%
“…Virtually all tumors with this expression pattern possessed co-amplification of a region on 8q22–24 that includes RPL8 , RPL30 , and the oncogenes MYC and PVT1. Amplification of this region has been previously described in breast cancers and correlates with chemoresistance and metastasis [ 36 , 37 , 45 47 ]. Our results indicate that this amplification and the ensuing overexpression of RPL8 and RPL30 also occurs in subsets of melanoma, liver, prostate, lung, and head and neck cancers.…”
Section: Discussionmentioning
confidence: 99%